Motivational incentives modulate age differences in visual perception - Spaniol, Julia; Voß, Andreas; Bowen, Holly J.; Grady, Cheryl L. (Psychology and aging, 2011)
This study examined whether motivational incentives modulate age-related perceptual deficits. Younger and older adults performed a perceptual discrimination task in which bicolored stimuli had to be classified according to their dominating color. The valent color was associated with either a positive or negative payoff, whereas the neutral color was not associated with a payoff. Effects of incentives on perceptual efficiency and response bias were estimated using the diffusion model (Ratcliff, 1978). Perception of neutral stimuli showed age-related decline, whereas perception of valent stimuli, both positive and negative, showed no age difference. This finding is interpreted in terms of preserved top-down control over the allocation of perceptual processing resources in healthy aging. (PsycINFO Database Record (c) 2016 APA, all rights reserved)